Pengaruh Media Pengasapan terhadap Kualitas Eksterior dan Organoleptik Telur Asin Asap - Eva Fajriana; Achmad Djaelani; Aam Gunawan (Rawa Sains: Jurnal Sains STIPER Amuntai, 2020)
Duck eggs that are often processed into salted eggs. But now it is necessary to look for other alternatives from processing these duck eggs with different tastes, besides taste salty there is also a sense of smoked.This study aims to analyze the effect of fumigation media on the exterior quality and organoleptic of salted smoked eggs. The method was used an experimental method. Fumigation was carried out 48 hours for each fumigation media. The research method used a Completely Randomized Design (CRD) with five treatments and four replications (5x4) in a total of 20 research units consist of m0 = no fumigation (control), m1 = fumigation media using coconut fiber, m2 = fumigation media using sawdust, m3 = fumigation media using rice husk, and m4 = fumigation media using galam bark. Exterior quality data obtained were carried out by homogeneity test data and ANOVA. If the analysis of variance is significantly different or very real it's done by means of the middle value test using the Duncan Multiple Range Test (DMRT). While the analysis of the organoleptic test results obtained was performed using the Kruskal Wallis test then Duncan Multiple Range Test (DMRT). The results showed that the fumigation media effected to the sand and the typical aroma of salted smoked eggs. The fuming media acts on the weight reduction of salted smoked eggs. Galam bark fuming media and coconut fiber has the highest sandiness among other media. However, the smoked media from galam bark had the biggest egg weight shrinkage.